2009
DOI: 10.1002/bbb.188
|View full text |Cite
|
Sign up to set email alerts
|

Commercializing lignocellulosic bioethanol: technology bottlenecks and possible remedies

Abstract: With diminishing oil supplies and growing political instability in oil-producing nations, the world is facing a major energy threat which needs to be solved by virtue of alternative energy sources. Bioethanol has received considerable attention in the transportation sector because of its utility as an octane booster, fuel additive, and even as neat fuel. Brazil and the USA have been producing ethanol on a large scale from sugarcane and corn, respectively. However, due to their primary utility as food and feed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
183
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(192 citation statements)
references
References 108 publications
1
183
0
8
Order By: Relevance
“…These results showed that there was a higher concentration of ethanol when B. cereus was used to degrade the sesame seed residues, which suggested there was a higher conversion of the substrate to reducing sugars. Banerjee et al (2010) explained that enzymatic hydrolysis is done by cellulase enzymes that are highly substrate specific. The obtained yield can be compared with the yield obtained from other wild-type bacteria.…”
Section: Bioethanol Production From the Saccharification And Fermentamentioning
confidence: 99%
“…These results showed that there was a higher concentration of ethanol when B. cereus was used to degrade the sesame seed residues, which suggested there was a higher conversion of the substrate to reducing sugars. Banerjee et al (2010) explained that enzymatic hydrolysis is done by cellulase enzymes that are highly substrate specific. The obtained yield can be compared with the yield obtained from other wild-type bacteria.…”
Section: Bioethanol Production From the Saccharification And Fermentamentioning
confidence: 99%
“…Moreover, no inhibitory by-product is formed in enzymatic hydrolysis [30]. However, enzymatic hydrolysis is carried out by cellulase enzymes that are highly substrate specific [31]. Here cellulase and hemicellulase enzymes cleave the bonds of cellulose and hemicellulose respectively (Cellulose contains glucan and hemicellulose contains different sugar units such as mannan, xylan, glucan, galactan and arabinan).…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…This allows switching between products according to market conditions, which is practised in some Brazilian sugar mills, and has also been suggested for sweet sorghum processing in Northern China [100]. Potential benefits of combined fermentation -distillation processes for ethanol production from lignocellulose may include (i) replacing exogenous nutrient supplements with sugar juice and/or molasses, which are rich in nutrients [88], (ii) mixing of sugars from juice and lignocellulose to increase ethanol concentrations at the end of the cellulose fermentation, and (iii) scale-up of ethanol purification/distillation to achieve economies of scale and improve energy efficiency [99]. Similar integration possibilities also exist in grain (small grains, corn, etc.)…”
Section: 23mentioning
confidence: 99%